Isu Pendidikan Islam di Era Globalisasi - Ahmad Yasir Al Amin; Sukari Sukari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Globalization, recognized as a defining phenomenon of the 21st century, has profoundly influenced numerous aspects of life, including Islamic education. This article seeks to critically analyze the challenges confronting Islamic education in the context of globalization, assess its impacts, and propose strategic solutions. Employing a systematic literature review method within a qualitative framework, the study explores diverse perspectives to uncover actionable insights. The findings underscore the urgent need to integrate Islamic values into educational curricula, harness technological advancements to enhance learning, and adopt a comprehensive approach that harmonizes religious principles with global dynamics.